1999
DOI: 10.2135/cropsci1999.0011183x003900020040x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Response to Harmone‐Containing Product in Kentucky Bluegrass Subjected to Drought

Abstract: The purpose of this study was to determine if exogenous hormonecontaining products (HCP) (seaweed extract and humic acid) enhance endogenous antioxidant concentration in Kentucky bluegrass (Poa pratensis L.) subjected to drought. Two‐week‐old seedlings of Kentucky bluegrass (cv. Plush) were treated with seaweed extract at 326 g ha−1, humic acid (25% active) at 5 L ha−1, alone or in combination, and grown under two soil moisture levels (−0.03 MPa and −0.5 MPa) for 5 wk, and subsequently analyzed for antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
74
1
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 0 publications
15
74
1
4
Order By: Relevance
“…A high level of antioxidant in Sitreated bentgrass can condition turfgrass to tolerant environmental stress (Zhang and Schmidt, 1999).…”
Section: Superoxide Dismutase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…A high level of antioxidant in Sitreated bentgrass can condition turfgrass to tolerant environmental stress (Zhang and Schmidt, 1999).…”
Section: Superoxide Dismutase Activitymentioning
confidence: 99%
“…Zhang and Schmidt (1999) reported that bentgrass with a high level of antioxidant such as Superoxide dismutase produced better turf quality. Silicate has been shown to enhance plant growth and reduced severity of fungal diseases of creeping bentgrass (Gussack et al, 1998;Uriarte and Bowman, 1996), rice (Datnoff et al, 1991), and cucumber (Belanger et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…12.7 and 4.8%, respectively. [7,28] Because of these qualities, DMF, a polar solvent, demonstrated limited improvement compared with acetone for extraction of this particular pigment. After the initial 20 min of stirring, the extracts treated with DMF were noticeably darker green and had less green tissue remaining than extracts with acetone.…”
Section: Resultsmentioning
confidence: 99%
“…Significant increases in superoxide oxidase and ascorbate peroxidase content were also noted in different genotypes of fescue under water‐deficit; again, the extent of the increase was dependent on the extent of their drought resistance (Sarmast et al., ). Kentucky bluegrass, in contrast, showed no significant effect of drought stress on leaf superoxide dismutase activity (Zhang & Schmidt, ). Da Costa and Huang () reported a consistent decrease in both superoxide dismutase and catalase activities in the leaves of creeping bentgrass when exposed to prolonged water‐deficit, and similar decreases in superoxide dismutase expression were reported in the roots of drought‐stressed creeping bentgrass (Xu et al., ).…”
Section: Effects Of Drought On Metabolism Of Cool‐season Grassesmentioning
confidence: 99%